New hopes for the breast cancer treatment: perspectives on the oncolytic virus therapy - Chowaniec, Hanna; Ślubowska, Antonina; Mroczek, Magdalena; Borowczyk, Martyna; Braszka, Małgorzata; Dworacki, Grzegorz; Dobosz, Paula; Wichtowski, Mateusz (Frontiers in Immunology, 2024)
Oncolytic virus (OV) therapy has emerged as a promising frontier in cancer treatment, especially for solid tumours. While immunotherapies like immune checkpoint inhibitors and CAR-T cells have demonstrated impressive results, their limitations in inducing complete tumour regression have spurred researchers to explore new approaches targeting tumours resistant to current immunotherapies. OVs, both natural and genetically engineered, selectively replicate within cancer cells, inducing their lysis while sparing normal tissues. Recent advancements in clinical research and genetic engineering have enabled the development of targeted viruses that modify the tumour microenvironment, triggering anti-tumour immune responses and exhibiting synergistic effects with other cancer therapies. Several OVs have been studied for breast cancer treatment, including adenovirus, protoparvovirus, vaccinia virus, reovirus, and herpes simplex virus type I (HSV-1). These viruses have been modified or engineered to enhance their tumour-selective replication, reduce toxicity, and improve oncolytic properties. Newer generations of OVs, such as Oncoviron and Delta-24-RGD adenovirus, exhibit heightened replication selectivity and enhanced anticancer effects, particularly in breast cancer models. Clinical trials have explored the efficacy and safety of various OVs in treating different cancers, including melanoma, nasopharyngeal carcinoma, head and neck cancer, and gynecologic malignancies. Notably, Talimogene laherparepvec (T-VEC) and Oncorine have. been approved for advanced melanoma and nasopharyngeal carcinoma, respectively. However, adverse effects have been reported in some cases, including flu-like symptoms and rare instances of severe complications such as fistula formation. Although no OV has been approved specifically for breast cancer treatment, ongoing preclinical clinical trials focus on four groups of viruses. While mild adverse effects like low-grade fever and nausea have been observed, the effectiveness of OV monotherapy in breast cancer remains insufficient. Combination strategies integrating OVs with chemotherapy, radiotherapy, or immunotherapy, show promise in improving therapeutic outcomes. Oncolytic virus therapy holds substantial potential in breast cancer treatment, demonstrating safety in trials. Multi-approach strategies combining OVs with conventional therapies exhibit more promising therapeutic effects than monotherapy, signalling a hopeful future for OV-based breast cancer treatments.